A Study of Impact of Cloud Computing and Artificial Intelligence on Banking Services, Profitability and Operational Benefits - Dr. Sunil Joshi, Sadhana Tiwari, Shashank Bharadwaj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Banks have seen a convergence in end-customer banking interactions over the last decade, owing to IT-enabled solutions and services such as Core Banking, Online Banking, Mobile Banking, Wallet, Wallets Kiosk Banking. The evolution of IT in the banking industry supports both banks and their clients. Banks' business models are now centered on delivering consumer joy via IT-enabled solutions and services. Cloud technology allows banks to follow a digital paradigm for providing novel channels, reducing TAT to market new offerings, fulfilling consumer expectations, and adhering to regulatory requirements at a lower cost. In constantly evolving technical paradigms, cloud-based solutions offer a higher value proposition to IT solutions and services. Device administrators can remotely assemble, upload, customize, and execute virtual tools to manage a business solution using cloud infrastructure. Furthermore, cloud IT technology can be scaled up or down at any time based on planned use and specifications without incurring high costs. To assess the impact of cloud computing and artificial intelligence in operational and service advantage Confirmatory factor analysis (CFA) technique is used. The thesis demonstrates how well the measured variables reflect the number of constructs and whether the estimation hypothesis is confirmed or rejected.